Résultats internationaux de ski de fond. Evolution de la compétition entre les nations de 2006 à 2019 - Renaud, A.; Kempf, H. (2019)
The objective of nations is to win as many medals (top 3) and diplomas (top 8) as possible in major international competitions such as the Olympic Games or World Championships. An overview of the international results allows the nations to situate themselves in relation to the other nations. In this study, we provide an overview of cross-country skiing results between 2006 and 2019 at the Olympic Games, as well as at the Elite and Junior World Championships. One of the objectives is to study the development of the competition, as well as to identify the most successful nations; for both men and women. The ages of diploma-winning athletes were also documented. The sports results from the Infostrada Podium Performance database were used for the study. The analysis followed a descriptive approach to present the market for medals and diplomas, a count of diplomas by nation as well as age distribution. The results identified in particular an increase in competition at the elite level, especially among women, the existence of dominant nations in improvement (e. g. Norway) or rather in decline (e. g. Sweden among men), as well as a slight tendency to have younger diplomas-winning athletes at the World Championships compared to the Olympic Games.